Growth and Production Responses of Cabbage (Brassica oleracea L.) after Various Bat Guano Fertilizer Application Doses in Lowlands - Rahman Hairuddin; Andi Safitri Sacita*; Oktafianus Toricelin (Agrotech Journal, 2023)
Cabbage is a popular horticultural commodity in the community with great potential development in highlands and lowlands. Nutrient fulfillment is a factor that supports optimal cabbage growth and production. This study aimed to determine the effect of different bat guano fertilizer doses on the growth and production of cabbage in lowlands. The cabbage type used was a suitable variety at lowlands called Grand 22. This study was performed in the experimental land of the Faculty of Agriculture, UNCP at 2 masl on September – December, 2021, through a randomized group design with six treatments and four replications. The treatments included: P0 = Control (without bat guano treatment), P1 = 30 g of bat guano per crop, P2 = 60 g of bat guano per crop, P3 = 90 g of bat guano per crop, P4 = 120 g of bat guano per crop, and P5 = 150 g of bat guano per crop. The results indicate that bat guano significantly affects all observed parameters. The 150 g of bat guano per crop provides the best effect on the cabbage height (27.75 cm), leaf width (27 cm), crop-forming age (36.5 days), and crop weight (1106.5 g).